From ”naked country” to ”sheltering ice”: Rudy Wiebe’s Revisionist Treatment of John Franklin’s First Arctic Narrative - Birkwood, Susan (Nordlit, 2008)
Rudy Wiebe's A Discovery of Strangers (1994) offers a revisionist construction of Franklin's first expedition to find the North-West Passage, one that attempts to show the disparate views of the landscape held by the British explorers and the Yellowknife of the Coppermine region-one of the Dene peoples-and to sound a warning about the devastating effects of the arrogant will to dominate the environment. True to the conventions of historical fiction, Wiebe, makes Franklin, himself, a largely peripheral figure, choosing to focus on lesser known participants in the events of 1821.